Pengukuran Kinerja Menggunakan Pendekatan Balanced Scorecard Untuk Pengambilan Keputusan (Studi Kasus Pada PT Mayora Indah Tbk Periode 2017-2021) - Astuti Astuti; Indupurnahayu Indupurnahayu; Hurriyaturrohman Hurriyaturrohman (Departement of Mathematics Education, 2024)
This study aims to measure the performance of PT Mayora Indah Tbk with Balanced Scorecard from a financial perspective, customer perspective, internal business process perpective, and learning and growth perspective for decision making. The result of this study indicate that the performance of PT Mayora Indah Tbk for the 2017-2021 period is in a poor condition, this is due to the calculation result from each perspective, from a financial perspective showing poor result in the calculation of ROE, ROA, and Operating Income which are far from the established industy standards, the customer shows that the company’s performance is quite good due to the balanced of cash receipts from customers, the internal business process perspective shows unfavorable result due to a decrease in operating profit from 2020-20221 coinciding with Covid-19, and the growth and learning perspective shows unfavorable result due to an increase in the number of employees, but the net profit generated has not been maximized this is shown in 2021